Arginase activity in the blood of patients with visceral leishmaniasis and HIV infection. - Yegnasew Takele; Tamrat Abebe; Teklu Weldegebreal; Asrat Hailu; Workagegnehu Hailu; Zewdu Hurissa; Jemal Ali; Ermiyas Diro; Yifru Sisay; Tom Cloke; Manuel Modolell; Markus Munder; et al. (Public Library of Science (PLoS), 2013)
Visceral leishmaniasis is a parasitic disease associated with high mortality. The most important foci of visceral leishmaniasis in Ethiopia are in the Northwest and are predominantly associated with high rates of HIV co-infection. Co-infection of visceral leishmaniasis patients with HIV results in higher mortality, treatment failure and relapse. We have previously shown that arginase, an enzyme associated with immunosuppression, was increased in patients with visceral leishmaniasis and in HIV seropositive patients; further our results showed that high arginase activity is a marker of disease severity. Here, we tested the hypothesis that increased arginase activities associated with visceral leishmaniasis and HIV infections synergize in patients co-infected with both pathogens.We recruited a cohort of patients with visceral leishmaniasis and a cohort of patients with visceral leishmaniasis and HIV infection from Gondar, Northwest Ethiopia, and recorded and compared their clinical data. Further, we measured the levels of arginase activity in the blood of these patients and identified the phenotype of arginase-expressing cells. Our results show that CD4(+) T cell counts were significantly lower and the parasite load in the spleen was significantly higher in co-infected patients. Moreover, our results demonstrate that arginase activity was significantly higher in peripheral blood mononuclear cells and plasma of co-infected patients. Finally, we identified the cells-expressing arginase in the PBMCs as low-density granulocytes.Our results suggest that increased arginase might contribute to the poor disease outcome characteristic of patients with visceral leishmaniasis and HIV co-infection.